From Commercial Space to the Space of Thought: The Practices of Independent Bookstores in Thai Society - Sanguansak, Pongsakorn (Journal of Social Sciences Naresuan University, 2026)
This article examines the roles and survival strategies of independent bookstores in Thai society amid a dramatic decline in physical bookstores—from 2,483 to approximately 800 over the past decade (c. 2014–2022)—despite increasing reading rates among Thai people and a book market valued at over 20 billion baht in 2025. The study employs four conceptual frameworks: bookstores as spaces for ideological negotiation, as social and cultural spaces, as socially connective retail, and survival strategies in local contexts. These frameworks were applied through case studies of four independent bookstores: Ran Lao Bookshop (Chiang Mai), House of Commons (Bangkok), Raan Nang Seu Lek Lek (Chiang Mai), and Philadelphia Bookstore (Ubon Ratchathani). The findings reveal that independent bookstores function as more than mere commercial establishments, serving as vital learning spaces that provide safe environments for developing critical consciousness, as counterspaces that challenge capitalist logic, and as informal schools that cultivate analytical and socially engaged citizens. However, these bookstores face significant challenges originating from inequitable industry structures, supply chain monopolization, and inadequate government support. The article proposes partnership-based policy recommendations, including implementing cultural vouchers, structural reforms to ensure fair competition in the industry, direct support for independent bookstores, and establishing a national book institute. These measures aim to preserve independent bookstores as cultural assets that Thai society cannot afford to lose.